Тепломассоперенос в подогреваемой снизу свободной цилиндрической элементарной конвективной ячейке с косинусоидальным профилем дна - Бозбей, Л. С.; Костиков, А. О.; Ткаченко, В. И. (Национальный технический университет "Харьковский политехнический институт", 2017)
Розглянуто задачу про теплову конвекцію в'язкої нестисливої рідини у циліндричній елементарній конвективній комірці з косіносуїдально поглибленим дном та вільними граничними умовами. Побудовано функції Стокса у циліндричній вільній конвективній комірці з неплоскими межами. На підставі ефекту Фудзівари отримано модельні розподіли ліній струму Стокса та обуреної температури у циліндричній елементарній конвективній комірці з неплоским профілем дна.

The problem of thermal convection of a viscous incompressible fluid in a cylindrical elementary convective cell with a cosine bottom and free boundary conditions is considered. The analytical solutions of a stationary linear Rayleigh problemin the case of free boundary conditions as basic functions should be used. The spatial field distribution of the flow velocities in the cell with cosine bottom is defined. Stokes’ functions are built in a cylindrical free convective cell with plane boundaries and in the cosine cavity bottom as well. Current lines distributions in cells with different model functions are qualitatively alike; different model functions of current lines differ in the numerical value of their maximum. The distribution model Stokes’ streamlines temperature perturbations in a cylindrical elementary convective cell with a cosine bottom and free boundary conditions is obtained based on the Fujiwara effect.
Heat and mass transfer in the heated from below elementary convective cell with free boundaries and cosine bottom
Keywords: температура; элементарная конвективная ячейка; функции Бесселя; эффект Фудзивары; линии Стокса